Pengaruh Komunikasi Interpersonal dan Self Regulated Learning terhadap Hasil Belajar Siswa - Ria Setyawati Utami Sinaga; Sudarno Sudarno; Leny Noviani (Journal on Education, 2023)
This study's objective was to ascertain the effect of interpersonal communication and self regulated learning on student learning outcomes for Economics and Business subjects at State Vocational Schools in Klaten, namely, among others, State Vocation School 1 Jogonalan, State Vocation School 1 Juwiring, State Vocation School 1 Klaten, State Vocation School 4 Klaten, and State Vocation School 1 Pedan. Class XI students that are actively participating in the study employ a quantitative descriptive methodology, at State Vocational High Schools in Klaten who have the competence for daring business skills and marketing in the 2021-2022 academic year. The total population of this study was 345 students. Proportional random sampling was the approach of choice for this study's sample., which resulted in a sample of 187 students. The techniques used for data collection are questionnaires and documentation. Multiple linear regression analysis was the method of data analysis employed in this investigation..The findings of this research showed that: 1) interpersonal communication has a positive and significant impact on student learning outcomes. 2) Self regulated learning affects learning outcomes in a beneficial and significant way. 3) Interpersonal communication and self regulated learning have a positive and significant impact on student learning outcomes